Lead-free radiation shielding sheet and its manufacturing method
Patent Information
- Application Number
- CN202611106649.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-02-20
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
上述现有技术虽然在无需使用铅即可实现放射线屏蔽以谋求轻量化方面具有一定的意义,但其主要屏蔽机制依赖于锡、碘和锑等金属或准金属元素,因此难以视为非金属复合屏蔽组合物
[0030]根据本发明的一个实施例,通过不在高分子基体中使用铅及高密度金属(Pb、W和Mo),而是采用包含医用级硫酸钡、三氧化二铋、三氧化二铝及碳酸钙的无机填料组合物,相较于现有单独使用硫酸钡的组合物,实现显著提高的放射线屏蔽性能。
Smart Images

Figure CN122991705A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a radiation shielding technology capable of shielding medical institutions and hospitals from low-dose X-rays (30kV) to high-dose X-rays (120kV). More specifically, this invention relates to a lead-free radiation shielding sheet and its manufacturing method. This shielding sheet does not use harmful lead (Pb) or high-density heavy materials such as tungsten (W) and molybdenum (Mo), making it an environmentally friendly material harmless to humans. It also allows for lightweight manufacturing. Furthermore, this shielding sheet ensures that it achieves a shielding performance exceeding the specified level for radiation within the voltage range of 30kV to 120kV medical X-ray tubes. It can replace existing radiation shields, protective clothing, and shielding sheets using heavy materials and can be used in medical and industrial fields. Background Technology
[0002] Radiation is indispensable in medical diagnosis and treatment, but it can have harmful effects on the human body, thus requiring shielding technologies that can block radiation exposure. In particular, hospitals, medical examination centers, and mobile diagnostic equipment are experiencing a continuous increase in demand for shielding sheets, curtains, and protective clothing used to shield X-rays.
[0003] Existing radiation shielding technologies are mainly based on the use of high-density metallic materials such as lead (Pb), tungsten (W), and molybdenum (Mo) to absorb and attenuate radiation.
[0004] While these metallic shielding materials offer the advantage of high shielding performance, they also have drawbacks such as heavy weight, poor processability, and potential harm to human health and environmental pollution.
[0005] Therefore, in recent years, research on environmentally friendly and lightweight shielding materials to replace lead has been actively promoted.
[0006] In response to this trend, non-metallic radiation shielding sheets using polymer resins (such as silicone, ethylene-propylene-diene monomer (EPDM), rubber, etc.) as the matrix, mixed with inorganic fillers such as barium sulfate (BaSO4) and bismuth compounds, or radiation shielding sheets that do not use lead or high-density metals (Pb, W, and Mo), have been proposed. Using lead-free or non-metallic fillers that do not contain lead or high-density metals (Pb, W, and Mo) offers advantages over metals, ensuring lightweight and flexibility while reducing the burden on human health and the environment.
[0007] However, traditional shielding sheet technology often relies on a single filler or a limited combination, which has the limitation of making it difficult to guarantee a sufficient shielding rate within the voltage range of medical X-ray tubes (approximately 30~120kV).
[0008] For example, while barium sulfate alone can achieve the specified level of shielding, it may not reach the shielding rate required for actual medical environments.
[0009] Furthermore, when using multiple inorganic fillers in combination, problems such as uneven mixing due to chemical reactions or poor dispersion between the fillers, or quality degradation during molding, can occur. In particular, it has been confirmed that when using industrial-grade barium sulfate, a chemical reaction occurs during mixing with bismuth oxide, resulting in poor stirring, which poses a significant obstacle in the actual manufacturing process of shielding sheets.
[0010] On the other hand, Korean Patent Publication No. 10-1103850 (hereinafter referred to as "Prior Art") discloses a lead-free rubber radiation shield and its manufacturing method, which uses synthetic or natural rubber as a polymer matrix and mixes tin (Sn), iodine (I2), and antimony (Sb) in powder form to achieve radiation shielding. While the aforementioned Prior Art has some significance in achieving radiation shielding without the use of lead, thus aiming for weight reduction, its main shielding mechanism relies on metallic or quasi-metallic elements such as tin, iodine, and antimony, and therefore cannot be considered a non-metallic composite shielding composition. Furthermore, in this Prior Art, barium sulfate is not used as the main component of the composite shielding composition, but only as an auxiliary structure coated on the surface of a rubber layer mixed with tin, iodine, and antimony, and it completely ignores the purity differences of barium sulfate itself, as well as its stability when mixed with other inorganic fillers. In particular, the Prior Art does not offer specific technical ideas or experimental verification regarding the stability, coagulation, or gelation problems of the combination of medical-grade barium sulfate and bismuth trioxide during stirring, and the resulting uniformity of shielding performance.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Korean Patent Publication No. 10-1103850 (January 2, 2012) Summary of the Invention
[0014] The problem the invention aims to solve
[0015] The technical problem to be solved by the present invention is to provide a lead-free radiation shielding sheet and its manufacturing method, which does not require the use of high-density metals such as lead and can ensure excellent shielding performance in the field of medical X-ray.
[0016] The technical problem to be solved by the present invention is to provide a lead-free radiation shielding sheet and its manufacturing method. The lead-free radiation shielding sheet uses a variety of inorganic fillers that do not contain lead or high-density metals (Pb, W and Mo), and there is no chemical reaction between the fillers and no problem of poor mixing, so that stable manufacturing can be achieved.
[0017] The technical problem to be solved by the present invention is to provide a lead-free radiation shielding sheet and its manufacturing method, which can simultaneously achieve lightweight, flexibility and environmental friendliness.
[0018] means for solving problems
[0019] As a technical solution to the aforementioned technical problem, the present invention provides a lead-free radiation shielding sheet, characterized in that it comprises: a polymer matrix containing one or more selected from silicone, ethylene-propylene-diene monomer (EPDM), rubber, thermoplastic elastomer (TPE), and thermoplastic polyurethane (TPU); and a composite shielding composition dispersed within the polymer matrix, wherein the composite shielding composition must contain medical-grade barium sulfate (BaSO4) and bismuth trioxide (Bi2O3), and also contains one or more selected from aluminum oxide (Al2O3) and calcium carbonate (CaCO3). The medical-grade barium sulfate remains inert during melt mixing with the bismuth trioxide, thereby being uniformly dispersed within the polymer matrix.
[0020] In one embodiment, the medical-grade barium sulfate has a purity of over 99% and maintains fluidity within a temperature range of 60°C to 250°C without undergoing a gelation reaction caused by impurities.
[0021] In one embodiment, based on the total weight of the lead-free radiation shielding sheet, the composite shielding composition may also contain 10 wt% to 35 wt% of the medical-grade barium sulfate, 15 wt% to 40 wt% of the bismuth trioxide, 5 wt% to 10 wt% of the aluminum trioxide, and 2.5 wt% to 5 wt% of the calcium carbonate.
[0022] In one embodiment, the lead-free radiation shield may have a thickness of 1 mm to 5 mm and, under medical X-ray irradiation conditions with a tube voltage of 100 kV, may have a radiation shielding rate of over 93%.
[0023] In one embodiment, the lead-free radiation shielding sheet weighs 30% to 40% of the weight of a lead (Pb)-based shielding sheet and may have the flexibility to prevent the shielding layer from cracking when bent.
[0024] As another technical solution to the aforementioned technical problem, the present invention provides a method for manufacturing a lead-free radiation shielding sheet, comprising the following steps: (a) a polymer matrix preparation step; (b) a composite shielding composition preparation step, wherein the composite shielding composition contains medical-grade barium sulfate (BaSO4) which has chemical inertness when mixed with bismuth trioxide (Bi2O3); (c) a mixing step, wherein the composite shielding composition is added to the polymer matrix in a softened or molten state by heating, and dispersion is achieved solely by physical stirring without gelation or agglomeration; and (d) a step of shaping the mixed product into a sheet form.
[0025] In one embodiment, the heating in step (c) can be performed within a temperature range that ensures the melt flow of the polymer matrix and prevents the thermal decomposition of the polymer matrix.
[0026] In one embodiment, step (c) can also be performed by directly adding the medical-grade barium sulfate and the bismuth trioxide particles into the polymer matrix for mixing without separately coating the surface of the particles.
[0027] In one embodiment, the medical-grade barium sulfate has a purity of over 99% and can maintain fluidity in a temperature range of 60°C to 250°C without undergoing a gelation reaction caused by impurities.
[0028] In one embodiment, the composite shielding composition may also contain 10 wt% to 35 wt% barium sulfate, 15 wt% to 40 wt% bismuth trioxide, 5 wt% to 10 wt% aluminum trioxide, and 2.5 wt% to 5 wt% calcium carbonate, based on the total weight of the sheet.
[0029] The effects of the invention
[0030] According to one embodiment of the present invention, by not using lead and high-density metals (Pb, W and Mo) in the polymer matrix, but instead using an inorganic filler composition containing medical-grade barium sulfate, bismuth trioxide, aluminum oxide and calcium carbonate, a significantly improved radiation shielding performance is achieved compared to existing compositions that use barium sulfate alone.
[0031] According to one embodiment of the present invention, by using high-purity medical-grade barium sulfate, chemical reactions and poor stirring problems that may occur during mixing with bismuth trioxide can be prevented, thereby achieving uniform mixing and stable sheet forming. As a result, an excellent shielding effect of over 90% can be stably ensured in the field of medical X-rays.
[0032] According to one embodiment of the present invention, compared with lead-based shielding materials, the present invention can achieve significant weight reduction and provides excellent flexibility and processability by using polymer matrices such as silicone, EPDM, and rubber, thereby enabling it to be applied in various application fields such as medical protective tools, shielding curtains, and mobile shielding structures.
[0033] According to one embodiment of the present invention, the present invention, through melting, mixing, die extrusion and molding processes, is suitable for large-scale production and can freely adjust the shape and thickness of the product according to the application, thus having extremely high industrial applicability. Attached Figure Description
[0034] Figure 1 The diagram illustrates the test equipment, test specimens, and test environment used to verify the radiation shielding capability of each composition in this embodiment.
[0035] Figure 2 A flowchart illustrating a method for manufacturing a lead-free radiation shield according to Embodiment 2 of the present invention is provided.
[0036] Explanation of reference numerals in the attached figures
[0037] S100: Polymer Matrix Preparation Steps
[0038] S200: Preparation steps for composite shielding composition
[0039] S300: Mixing steps of polymer matrix and composite shielding composition
[0040] S400: Sheet Form Manufacturing Steps
[0041] S500: Foreign matter removal and slow cooling steps. Detailed Implementation
[0042] The following detailed description of some embodiments of the present invention is based on the accompanying drawings. However, this is not intended to limit the invention to any particular embodiment, and it should be understood that all modifications, equivalents, and substitutions incorporating the technical concept of the present invention are included within the scope of protection of the present invention.
[0043] In this specification, unless the context clearly indicates otherwise, singular expressions also include plural expressions.
[0044] In this specification, unless otherwise expressly stated otherwise, when a component is described as "having" or "comprises" a sub-component, it does not mean that other components are excluded, but may also include other components.
[0045] In this specification, "medical grade barium sulfate" refers to a grade with a purity of 98% or higher, preferably 99% or higher, and which has had impurities such as iron (Fe) and sulfides that can react with bismuth contained in industrial grade barium sulfate removed, thus possessing chemical stability.
[0046] <Example 1: Lead-free radiation shielding sheet>
[0047] The lead-free radiation shielding sheet according to Example 1 comprises a polymer matrix and a composite shielding composition dispersed in the polymer matrix.
[0048] 1. Polymer Matrix
[0049] The polymer matrix used as the substrate in this invention is composed of one or more mixtures selected from silicone, ethylene-propylene-diene monomer (EPDM), rubber, thermoplastic elastomer (TPE), and thermoplastic polyurethane (TPU). This polymer matrix imparts flexibility to the radiation shielding sheet, preventing cracks from forming in the shielding layer when the sheet is bent or folded, and also improving wearing comfort and ease of installation.
[0050] 2. Composite Shielding Composition
[0051] The polymer matrix contains a composite shielding composition for shielding radiation. The composite shielding composition contains medical grade barium sulfate (BaSO4) and bismuth trioxide (Bi2O3) as essential components, and also contains one or more of aluminum trioxide (Al2O3) and calcium carbonate (CaCO3).
[0052] (1) Inertness and dispersion characteristics of medical grade barium sulfate
[0053] One feature of this embodiment is that the barium sulfate used is medical-grade barium sulfate with a purity of 99% or higher. Ordinary industrial-grade barium sulfate contains impurities such as iron (Fe) and sulfides. When it comes into contact with bismuth trioxide during high-temperature melting and mixing, a chemical reaction occurs, leading to gelation or agglomeration. This is the main reason for poor dispersion within the sheet and reduced shielding performance.
[0054] In other words, when industrial-grade barium sulfate with relatively low purity is mixed with bismuth trioxide, the mixture may agglomerate or gel during the mixing process due to chemical reactions or the influence of impurities. This causes a sharp increase in viscosity and makes it difficult to stir smoothly. Such poor mixing leads to uneven dispersion of the composite shielding composition, which in turn causes deviations in the quality of the sheet and the shielding performance.
[0055] Conversely, the medical-grade barium sulfate used in this invention maintains chemical inertness (i.e., an inactive state) during melt mixing with bismuth trioxide. Therefore, even without the addition of additional dispersants or chelating agents, or without additional coating treatment on the particle surface, a uniform dispersed phase can be formed within the polymer matrix without gelation. This not only simplifies the manufacturing process but also allows the shielding particles to be arranged without gaps, thereby maximizing shielding efficiency.
[0056] (2) Composition ratio and shielding performance
[0057] Based on the total weight of the sheet, the composite shielding composition is preferably blended in the following proportions: 10 wt% to 35 wt% medical-grade barium sulfate, 15 wt% to 40 wt% bismuth trioxide, 5 wt% to 10 wt% aluminum trioxide, and 2.5 wt% to 5 wt% calcium carbonate. Compared to lead (Pb)-based shielding, radiation shielding sheets manufactured with this optimal blending ratio can achieve a weight reduction of approximately 30% to 40%.
[0058] For example, the mixing can be carried out using mixing devices such as internal mixers, extruders, and roller mixers. The mixture is then extruded from a mold, and the extruded mixture is shaped to produce a sheet. After the sheet produced in this way is separated from the mold, burrs or foreign objects can be removed, and it can be slowly cooled.
[0059] Furthermore, the sheet material of this embodiment, with a thickness ranging from 1mm to 5mm, can achieve a high radiation shielding rate of over 93% under X-ray irradiation conditions with a tube voltage of 100kV, which is mainly used in medical settings. This is because it overcomes the limitations of using a single material, and the components can exert complementary shielding effects at different energy bands.
[0060] In contrast, the medical-grade barium sulfate used in this embodiment, during the mixing process with bismuth trioxide, suppressed the agglomeration or gelation phenomena described above, allowing the composite shielding composition to be stably dispersed within the polymer matrix. This not only improves the mixing stability during manufacturing but also ensures that the manufactured sheet exhibits uniform shielding performance overall.
[0061] Table 1 shows the difference in radiation shielding performance between a sheet made from a combination of medical-grade barium sulfate and bismuth trioxide, including the present embodiment, and a sheet made from a combination of industrial-grade barium sulfate and bismuth trioxide.
[0062] Table 1 shows the comparison results of shielding performance (dose rate and shielding efficiency) of (i) sheets containing medical grade barium sulfate and bismuth trioxide (“bismuth trioxide μGy / s” column) and (ii) sheets containing industrial grade barium sulfate and bismuth trioxide (“ordinary bismuth μGy / s” column) under the same voltage (kVp), current (mAs) and thickness (mm) conditions.
[0063] Table 1
[0064]
[0065] According to Table 1, the radiation dose rate (μGy / s) transmitted through the sheet using medical-grade barium sulfate was lower than that of the sheet using industrial-grade barium sulfate across all intervals. Correspondingly, its shielding rate was consistently higher. For example, under conditions of 50 kVp and 1 mm, the transmitted dose rate of the sheet using medical-grade barium sulfate was measured to be 69.56 μGy / s, with a shielding rate of 0.8927 (approximately 89.27%); while the sheet using industrial-grade barium sulfate was measured to be 92.12 μGy / s, with a shielding rate of 0.8579 (approximately 85.79%).
[0066] Furthermore, under conditions of 60kVp and 2mm, the shielding efficiency of medical-grade barium sulfate sheets was 50.59 μGy / s (0.9502), while that of industrial-grade barium sulfate sheets was 82.52 μGy / s (0.9188). Even under conditions of 70kVp and 3mm, it was confirmed that medical-grade barium sulfate sheets exhibited 46.06 μGy / s (0.9653), while industrial-grade barium sulfate sheets showed 93.26 μGy / s (0.9297).
[0067] This indicates that medical-grade barium sulfate can maintain a stable dispersion during mixing with bismuth trioxide, thereby improving the actual radiation attenuation (absorption) efficiency of the composite shielding composition.
[0068] Figure 1The diagram illustrates the test equipment, test specimens, and test environment used to verify the radiation shielding capability of each composition in this embodiment.
[0069] like Figure 1 As shown, the radiation shielding performance evaluation in this embodiment was conducted using a medical X-ray imaging device, which was manufactured by a South Korean manufacturer.
[0070] The radiation dose was measured using a medical radiation meter (Raysafe X2, R / F sensor), manufactured by Fluke AG of Sweden.
[0071] The test samples used in the experiment were radiation shielding sheets made of silicone sheets with a thickness of 1 mm as the polymer matrix. Each sheet was used as a composite shielding composition to contain 50 wt% of any one of the following: medical grade barium sulfate, bismuth trioxide, aluminum trioxide, and calcium carbonate.
[0072] In other words, in order to compare the individual shielding performance of each composition, four radiation shielding samples with different composite shielding compositions were manufactured under the same thickness and polymer matrix conditions.
[0073] The experiment was conducted in Figure 1 The test was conducted under the conditions shown, and the test site was maintained as a laboratory environment.
[0074] The environmental conditions for the experiment were set as follows: temperature 25±3℃ and relative humidity 40±15%.
[0075] The X-ray equipment used had a tube voltage of 30–150 kV and an inherent filtration of 2.5 mm Al. During radiation irradiation, the distance between the sample and the tip of the X-ray tube was set to approximately 10 cm. Radiation shielding performance was evaluated under conditions of a tube voltage range of 50–100 kV and a 2.5 mm Al filter.
[0076] In this embodiment, the individual shielding capabilities of each composite shielding composition were quantitatively compared by measuring the radiation transmittance dose rate (μGy / s) of each composite shielding composition under the same test conditions. The results are shown in Tables 2 and 3 below.
[0077] Table 2 compares the radiation shielding performance (μGy / s) of each composite shielding composition (bismuth trioxide, medical-grade barium sulfate, calcium carbonate, and aluminum trioxide) when applied alone under the same test conditions.
[0078] Table 2
[0079]
[0080] As shown in Table 2, under all voltage (kVp) and thickness (mm) conditions, bismuth trioxide exhibited the lowest radiation transmittance rate compared to other compositions, confirming its superior radiation shielding performance when used alone. On the other hand, medical-grade barium sulfate exhibited a higher transmittance rate compared to bismuth trioxide, especially at a thickness of 1 mm, with a considerable amount of radiation transmitted. Therefore, it is evident that medical-grade barium sulfate, when used alone as a medical X-ray shielding material, has limitations in performance.
[0081] In addition, calcium carbonate and aluminum oxide exhibit higher radiation transmittance rates than medical-grade barium sulfate under all conditions, which confirms that their radiation shielding effect when used alone is very limited.
[0082] Specifically, under conditions of 50 kVp and 1 mm, the radiation transmission dose rate of bismuth trioxide was measured to be 69.56 μGy / s, while the measured values for medical-grade barium sulfate, calcium carbonate, and aluminum oxide were 302.1 μGy / s, 476.7 μGy / s, and 526.9 μGy / s, respectively. The individual shielding performance of each composition showed significant differences.
[0083] Similarly, under conditions of 60 kVp and 2 mm, bismuth trioxide also exhibited excellent shielding performance with a radiation transmission dose rate of 50.59 μGy / s, while the measured values for medical-grade barium sulfate, calcium carbonate, and aluminum oxide were 254.7 μGy / s, 608 μGy / s, and 705.8 μGy / s, respectively, all showing relatively low shielding performance.
[0084] This result indicates that using any single composite shielding composition alone is insufficient to meet the shielding performance requirements of medical lead-free radiation shielding sheets.
[0085] In other words, while bismuth trioxide exhibits excellent shielding performance when used alone, it has limitations in terms of cost, weight, and processing performance; while medical-grade barium sulfate, calcium carbonate, and aluminum trioxide alone provide insufficient shielding performance.
[0086] The limitations of this single composition experimentally confirm the technical background of the present invention, namely: the present invention combines multiple composite shielding compositions to make the advantages of each composition complement each other, thereby achieving excellent radiation shielding performance that cannot be achieved when used alone.
[0087] Table 3 compares the shielding rates (%) of radiation shielding sheets using each composite shielding composition (bismuth trioxide, medical-grade barium sulfate, calcium carbonate, and aluminum trioxide) under the same voltage (kVp), current (mAs), and thickness (mm) conditions, based on the aforementioned test conditions and shielding rate calculation formula.
[0088] For reference, the shielding rate is calculated according to the following mathematical formula 1.
[0089] [Mathematical Expression 1]
[0090] Shielding efficiency = (I1 - I2) / I1 × 100
[0091] Wherein, I1 and I2 are the ionization currents (A) measured by medical X-rays before and after the sample was placed.
[0092] When measuring the shielding rate, the sample is placed about 5 to 10 cm away from the front of the radiation irradiator, and the distance between the radiation irradiator and the measuring instrument is set to about 80 cm.
[0093] Table 3
[0094]
[0095] As shown in Table 3, under all test conditions, bismuth trioxide exhibited a higher shielding efficiency than other compositions, indicating its excellent radiation shielding performance when used alone. Conversely, medical-grade barium sulfate showed a significantly lower shielding efficiency than bismuth trioxide, especially at a thickness of 1 mm, where its shielding efficiency was only about 50%, indicating limitations in its performance when used alone as a medical radiation shield.
[0096] In addition, calcium carbonate and aluminum oxide exhibited lower shielding rates across the entire voltage and thickness conditions, confirming that their radiation shielding effectiveness when used alone is very limited.
[0097] Specifically, under conditions of 50kVp and 1mm, bismuth trioxide has a shielding efficiency of approximately 89.27%, while medical-grade barium sulfate, calcium carbonate, and aluminum oxide have shielding efficiencies of approximately 53.42%, 26.49%, and 18.75%, respectively.
[0098] In addition, under conditions of 70kVp and 3mm, the shielding efficiency of bismuth trioxide is about 96.53%, while the shielding efficiency of medical grade barium sulfate, calcium carbonate and aluminum oxide are about 84.20%, 48.19% and 38.33%, respectively, indicating that the shielding performance of each component varies significantly when used alone.
[0099] The results above show that radiation shielding sheets made of medical-grade barium sulfate and other compositions (bismuth trioxide, calcium carbonate, and aluminum trioxide) can achieve a medical radiation shielding rate of approximately 80% to 95% or more without using conventional radiation shielding materials such as lead (Pb), tungsten (W), molybdenum (Mo), tin (Sn), and antimony (Sb).
[0100] The radiation shielding sheet manufactured according to the method of the present invention can achieve a weight reduction of about 1 / 3 compared with existing high-density shielding sheets, and has extremely high applicability in the medical and industrial radiation shielding markets because it can be mass-produced and customized.
[0101] To verify the above performance, the present invention first confirms the individual shielding performance of each composite shielding composition through the aforementioned experiment, and then sets the mixing ratio that can obtain the best shielding efficiency based on the results, and then prepares multiple samples.
[0102] In particular, in order to evaluate the shielding performance of high-energy radiation in the 80-100kV band, which is mainly used in the diagnostic environment of medical institutions, a 3mm thick mixed sample was prepared for radiation shielding experiments.
[0103] Based on the total weight of the sheet, the composite shielding composition according to the present invention may contain the following proportions: 10wt% to 35wt% barium sulfate (BaSO4), 15wt% to 40wt% bismuth trioxide (Bi2O3), 5wt% to 10wt% aluminum trioxide (Al2O3), and 2.5wt% to 5wt% calcium carbonate (CaCO3).
[0104] This ratio range is set to compensate for the limitations of the shielding performance of a single composition while achieving high shielding efficiency stably in the high-energy radiation region.
[0105] The mixed samples prepared based on the aforementioned ratio range are as follows:
[0106] Sample 1 is a reference sample used for comparison, containing approximately 60 wt% medical-grade barium sulfate, and free of bismuth trioxide, calcium carbonate, and aluminum trioxide. That is, it is the sample used to confirm the shielding performance as a benchmark when medical-grade barium sulfate is used alone.
[0107] Sample 2 is an example prepared to confirm the combined effect of the present invention. Its mixing ratio is about 30 wt% medical grade barium sulfate, about 20 wt% bismuth trioxide, and a total of 10 wt% calcium carbonate and aluminum oxide (e.g., 5 wt% calcium carbonate and 5 wt% aluminum oxide).
[0108] Sample 3 is an example prepared to maximize the shielding performance of the high-energy radiation region. Its mixing ratio is approximately 35 wt% medical-grade barium sulfate, approximately 25 wt% bismuth trioxide, and a total of 5 wt% calcium carbonate and aluminum trioxide.
[0109] Sample 4 is an example that takes into account both shielding performance and the physical stability and processability of the sheet. It is formulated by mixing approximately 25 wt% of medical-grade barium sulfate, approximately 25 wt% of bismuth trioxide, and a total of 10 wt% of calcium carbonate and aluminum trioxide.
[0110] Table 4 shows the experimental results of evaluating the radiation shielding performance of different composition combinations under radiation conditions of 50~100kV (including the 80~100kV band mainly used in medical diagnostic environments) for samples 1 to 4 described above.
[0111] This experiment was conducted by fabricating each sample to a thickness of 3 mm and measuring the transmitted radiation dose (μGy) and the shielding rate based on it.
[0112] Table 4
[0113]
[0114] Table 4 shows that, based on the radiation transmitted dose (μGy) measured under a 3mm thickness, the radiation transmitted dose of Sample 1 (medical-grade barium sulfate 60wt%) at 50kV is approximately 15.14 μGy. The transmitted dose increases with voltage: approximately 23.83 μGy at 60kV, 34.57 μGy at 70kV, 42.67 μGy at 80kV, 48.64 μGy at 90kV, and 63.54 μGy at 100kV. Correspondingly, the shielding efficiency of Sample 1 is approximately 0.8409 (84.09%) at 50kV and approximately 0.7882 (78.82%) at 100kV, indicating limitations in its shielding performance in high-energy radiation regions.
[0115] In contrast, samples 2 to 4 (combined samples obtained by mixing medical-grade barium sulfate with bismuth trioxide and other auxiliary compositions) showed significantly lower radiation transmission dose (μGy) throughout the voltage range.
[0116] For example, under 50kV conditions, the transmitted doses of samples 2, 3, and 4 are approximately 0.794μGy, 0.595μGy, and 0.868μGy, respectively. Correspondingly, the shielding efficiencies are approximately 0.9917 (99.17%), 0.9937 (99.37%), and 0.9909 (99.09%), respectively.
[0117] In addition, the combined sample still maintains excellent performance in the 80~100kV band, which is crucial in the diagnostic environment of medical institutions.
[0118] Specifically, under 100 kV conditions, the transmitted doses of samples 2, 3, and 4 were approximately 18.97 μGy, 19.72 μGy, and 20.38 μGy, respectively. These values were significantly lower than the approximately 63.54 μGy of sample 1.
[0119] Therefore, the shielding rates of samples 2 to 4 were calculated to be approximately 0.9368 (93.68%), 0.9343 (93.43%), and 0.9321 (93.21%), respectively, indicating that they all stably ensured excellent shielding performance of over 90%.
[0120] The above experimental results demonstrate that, according to the composite shielding composition of the present invention, when multiple compositions are used in combination within the mixing range of 10wt% to 35wt% barium sulfate, 15wt% to 40wt% bismuth trioxide, 5wt% to 10wt% aluminum trioxide, and 2.5wt% to 5wt% calcium carbonate, a significantly improved shielding performance can be achieved even in high-energy medical radiation areas, which is impossible to achieve when using a single composition alone.
[0121] In particular, the results of samples 2 to 4 show that the sheet manufactured according to the composition ratio of the present invention can stably maintain a shielding rate of more than 93% (Shielding rate: 0.93 or more) under 100kV conditions.
[0122] <Example 2>
[0123] Figure 2 A flowchart illustrating a method for manufacturing a lead-free radiation shield according to Embodiment 2 of the present invention is provided. The manufacturing method of Embodiment 2 is characterized by employing a "one-pot" physical mixing process.
[0124] like Figure 2 As shown, the method of this embodiment includes: a polymer matrix preparation step (S100), a composite shielding composition preparation step (S200), a polymer matrix and composite shielding composition mixing step (S300), a sheet form manufacturing step (S400), and a foreign matter removal and slow cooling step (S500).
[0125] The polymer matrix preparation step (S100) is a step of preparing a polymer matrix as a sheet matrix, wherein the polymer matrix includes silicone, EPDM, rubber, TPE, TPU, etc.
[0126] The polymer matrix can be selected based on the flexibility, heat resistance, and moldability of the sheet. For example, it can be composed of one or more of silicone resins, EPDM, and rubber. If necessary, the polymer matrix can be cut to specified sizes or pre-mixed for uniform blending.
[0127] The composite shielding composition preparation step (S200) is a step of preparing a shielding composition containing medical-grade barium sulfate, wherein the medical-grade barium sulfate is inert and will not cause a chemical reaction even when mixed with bismuth trioxide. At this time, the components can be prepared in powder form without separate surface coating treatment.
[0128] Specifically, in step (S200), a composite shielding composition comprising barium sulfate (BaSO4), bismuth trioxide (Bi2O3), aluminum trioxide (Al2O3), and calcium carbonate (CaCO3) is prepared.
[0129] The barium sulfate is medical-grade barium sulfate with a purity of over 99%, and it can be a raw material that, when mixed with the aforementioned bismuth trioxide, will not cause agglomeration or gelation due to chemical reaction, thus preventing the stirring process from being hindered.
[0130] In other words, in the process of mixing barium sulfate with bismuth trioxide in this embodiment, by suppressing the agglomeration of the mixture or the sharp increase in viscosity, the composite shielding composition can be stably dispersed in the polymer matrix.
[0131] In addition, the mixing ratio of the composite shielding composition can be set based on the test results described in Example 1 for confirming the individual shielding performance of each component and the shielding performance when combined.
[0132] For example, to ensure shielding performance against radiation in the 80-100kV band primarily used in diagnostic environments of medical institutions, the mixing ratio of barium sulfate, bismuth trioxide, calcium carbonate, and aluminum oxide can be selected based on the total weight of the sheet. Since the individual materials and test conditions of the composite shielding composition have been described in detail in Example 1, detailed descriptions are omitted in this step.
[0133] The step of mixing the polymer matrix and the composite shielding composition (S300) is to heat the polymer matrix and the composite shielding composition to mix them in a molten or softened state.
[0134] Specifically, the polymer matrix and the composite shielding composition are put into mixing devices such as internal mixers, extruders, and roller mixers, and heated and stirred to form a uniform mixture.
[0135] At this point, heating can be carried out within a temperature range (e.g., 60°C to 250°C) that ensures the melt flow of the polymer matrix to improve moldability, while preventing thermal degradation of the polymer. The composite shielding composition is then added to the molten matrix and kneaded. The mixing time, stirring speed, or feeding sequence can be adjusted as needed to improve the uniformity of the mixture.
[0136] In this step, medical-grade barium sulfate does not undergo a gelation reaction even when in contact with bismuth trioxide; therefore, the particles can be uniformly dispersed in the matrix simply by physical stirring. In particular, this invention has a process advantage: even without separate coating treatment (e.g., silica coating) on the particle surface, uniform dispersion can be achieved by direct mixing.
[0137] The sheet form manufacturing step (S400) is a step of manufacturing a sheet form with a target thickness (1 mm to 5 mm) by extruding or rolling the product that has been fully mixed in the mixing step (S300) through a die.
[0138] For example, the mixture can be formed into a sheet of a specified thickness by extrusion or molding, and the thickness of the sheet can be selected according to the specific requirements of medical radiation shielding.
[0139] The foreign matter removal and slow cooling step (S500) is a step in which the sheet manufactured into the sheet shape is separated from the mold, burrs or foreign matter are removed, and slow cooling is performed.
[0140] Specifically, by removing burrs and foreign matter that may remain on the edges or surface of the sheet after demolding, the appearance quality and safety of the product can be ensured. Furthermore, slow cooling improves the dimensional stability of the sheet. Slow cooling can be carried out at room temperature through natural cooling, or under controlled cooling conditions depending on the product characteristics, as needed.
[0141] Sheets manufactured using this method, thanks to the use of high-purity raw materials and uniform dispersion, can simultaneously ensure excellent shielding performance against high-energy X-rays and mechanical flexibility, even when thin.
[0142] While the present invention has been described above with reference to several embodiments, those skilled in the art will understand that various modifications and alterations can be made to the present invention without departing from the spirit and scope of the invention as set forth in the claims.
[0143] [This invention is based on a national research and development project]
[0144] [Project Number] 2420023464
[0145] [Project Number] 00468177
[0146] [Department Name] Ministry of Small and Medium Enterprises, Korea
[0147] [Name of Project Management (Specialty) Organization] Korea Small and Medium Enterprise Technology Information Promotion Agency
[0148] [Research Project Title] Entrepreneurial Growth Technology Development
[0149] [Research Topic Title] High-performance lens components utilizing direct-path low-reduction materials and development of medical low-reduction devices for fluoroscopic imaging that do not interfere with each other.
[0150] [Name of the organization implementing the project] Eight Margin Co., Ltd.
[0151] [Research Period] August 1, 2024 to July 31, 2025
Claims
1. A lead-free radiation shielding sheet, characterized in that, Include: The polymer matrix comprises one or more selected from silicone, ethylene-propylene-diene monomer (EPDM), rubber, thermoplastic elastomer (TPE), and thermoplastic polyurethane (TPU); and The composite shielding composition is dispersed within the polymer matrix. The composite shielding composition comprises medical-grade barium sulfate (BaSO4) and bismuth trioxide (Bi2O3), and also contains one or more selected from aluminum trioxide (Al2O3) and calcium carbonate (CaCO3). The medical-grade barium sulfate remains inert during the melt mixing with the bismuth trioxide and is uniformly dispersed within the polymer matrix.
2. The lead-free radiation shielding sheet according to claim 1, characterized in that, The medical-grade barium sulfate has a purity of over 99% and maintains fluidity within a temperature range of 60°C to 250°C without undergoing a gelation reaction caused by impurities.
3. The lead-free radiation shielding sheet according to claim 1, characterized in that, Based on the total weight of the lead-free radiation shielding sheet, the composite shielding composition comprises 10 wt% to 35 wt% of the medical-grade barium sulfate, 15 wt% to 40 wt% of the bismuth trioxide, 5 wt% to 10 wt% of the aluminum trioxide, and 2.5 wt% to 5 wt% of the calcium carbonate.
4. The lead-free radiation shielding sheet according to claim 3, characterized in that, The lead-free radiation shielding sheet has a thickness of 1 mm to 5 mm and a radiation shielding rate of over 93% under medical X-ray irradiation conditions with a tube voltage of 100 kV.
5. The lead-free radiation shielding sheet according to claim 1, characterized in that, The lead-free radiation shielding sheet weighs 30% to 40% of the weight of a lead (Pb)-based shielding sheet and has the flexibility to prevent the shielding layer from cracking when bent.
6. A method for manufacturing a lead-free radiation shielding sheet, characterized in that, include: (a) Polymer matrix preparation steps; (b) Preparation of composite shielding composition, wherein the composite shielding composition comprises medical grade barium sulfate (BaSO4) which is chemically inert when mixed with bismuth trioxide (Bi2O3). (c) The mixing step involves adding the composite shielding composition to the polymer matrix while it is heated to a softened or molten state, and dispersing it solely through physical stirring without gelation or agglomeration; and (d) The step of shaping the compounded product into a sheet.
7. The method for manufacturing a lead-free radiation shielding sheet according to claim 6, characterized in that, The heating in step (c) is carried out within a temperature range that ensures the melt flow of the polymer matrix and prevents the thermal decomposition of the polymer matrix.
8. The method for manufacturing a lead-free radiation shielding sheet according to claim 6, characterized in that, Step (c) involves directly mixing the medical-grade barium sulfate and bismuth trioxide particles into the polymer matrix without separately coating their surfaces.
9. The method for manufacturing a lead-free radiation shielding sheet according to claim 6, characterized in that, The medical-grade barium sulfate has a purity of over 99% and maintains fluidity within a temperature range of 60°C to 250°C without undergoing a gelation reaction caused by impurities.
10. The method for manufacturing a lead-free radiation shielding sheet according to claim 6, characterized in that, Based on the total weight of the sheet, the composite shielding composition comprises 10 wt% to 35 wt% barium sulfate, 15 wt% to 40 wt% bismuth trioxide, 5 wt% to 10 wt% aluminum trioxide, and 2.5 wt% to 5 wt% calcium carbonate.